2010
DOI: 10.1007/s10822-010-9399-4
|View full text |Cite
|
Sign up to set email alerts
|

Computer-assisted combinatorial design of bicyclic thymidine analogs as inhibitors of Mycobacterium tuberculosis thymidine monophosphate kinase

Abstract: Thymidine monophosphate kinase (TMPK(mt)) is an essential enzyme for nucleotide metabolism in Mycobacterium tuberculosis, and thus an attractive target for novel antituberculosis agents. In this work, we have explored the chemical space around the 2',3'-bicyclic thymidine nucleus by designing and in silico screening of a virtual focused library selected via structure based methods to identify more potent analogs endowed with favorable ADME-related properties. In all the library members we have exchanged the ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 59 publications
0
26
0
Order By: Relevance
“…Furthermore, we showed that hydroxylation of the 5-methyl group of the TMP substrate (3) resulted in a moderately potent TMPKmt inhibitor instead of substrate [5]. Mainly based on inhibitory data reported by our group, Frecer et al recently reported on the combinatorial design and structure-based in silico screening of a virtual focused library of bicyclic thymidine analogs in an effort to identify more potent TMPKmt inhibitors [6]. In their study they used the threedimensional structure of TMPKmt complexed with 5-hydroxymethyl-dUMP (3) to develop a QSAR model, to parameterize a target-specific scoring function for TMPKmt and to select virtual hits which display the highest predicted binding to the target.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…Furthermore, we showed that hydroxylation of the 5-methyl group of the TMP substrate (3) resulted in a moderately potent TMPKmt inhibitor instead of substrate [5]. Mainly based on inhibitory data reported by our group, Frecer et al recently reported on the combinatorial design and structure-based in silico screening of a virtual focused library of bicyclic thymidine analogs in an effort to identify more potent TMPKmt inhibitors [6]. In their study they used the threedimensional structure of TMPKmt complexed with 5-hydroxymethyl-dUMP (3) to develop a QSAR model, to parameterize a target-specific scoring function for TMPKmt and to select virtual hits which display the highest predicted binding to the target.…”
Section: Introductionmentioning
confidence: 86%
“…In this pilot study we decided to explore the importance of the proposed 5-CH 2 Figure 1 OH and 5'-modifications for TMPKmt inhibition. Selected promising TMPKmt inhibitors designed previously in our laboratory (1, 2, and 3) [4,5] or predicted by a QSAR model (4) [6]. K i exp and K i pre indicate experimental and predicted K i values, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…This Computational approach successfully narrows the filter and accelerates the process to new lead compounds compared with traditional synthesis approach. This was observed for peptide and peptidomimetic inhibitors of HIV-1 [16,17] and hepatitis C (HCV) [15] virus proteases design, for combinatorial design of bicyclic thymidine analogues [22] and complexation structure-based design of thymidine analogues [21,23] inhibitors of Mycobacterium Tuberculosis (MTb) thymidine monophosphate kinase, to provide insight into selectivity of peptidomimetic inhibitors with modified statine core for pf Plasmepsin II over human Cathepsin D [18]. Recently a complete process starting from the complexation QSAR model and its derived 3D-QSAR four features Pharmacophore (PH4) model have successfully served to screen a large Virtual Library of 1.6 million compounds reaching one hundred orally bioavailable pyrrolidine carboxamide inhibitors of MTb enoyl acyl carrier protein reductase (InhA) [24].…”
Section: Qsar Modelsmentioning
confidence: 89%
“…The complexation methodology has been described largely accor-ding to a procedure successfully used to elaborate one descriptor QSAR models of viral, bacterial and protozoal protease-inhibitor complexes and from them to design peptidomimetic, hydroxylnaphthoic, thymidine, triclosan and pyrrolidine carboxamide derivative inhibitors [15,16,17,18,19,20,21,22,23,24].…”
Section: Methodsmentioning
confidence: 99%
“…More recently attempts to replace the ribose ring with a phenyl [17] with no real improvement followed by a bicyclic sugar derivatives [18] reaching 3.5  μ M and later by a spacer ended by acyclic nucleoside analogues exploring edge to face interaction between the naphthyl group and Tyr39 has led to 0.27  μ M potency [19]. A Computer-assisted combinatorial design of bicyclic thymidine analogs as inhibitors of TMPK mt by Frecer et al [20] identified submicromolar concentration range inhibitors with favorable ADME profile.…”
Section: Introductionmentioning
confidence: 99%